Implications of genetic variability of Trypanosoma cruzi for the pathogenesis of Chagas disease Implicações da variabilidade genética do Trypanosoma cruzi na patogênese da doença de Chagas - Fernanda da Silva Manoel-Caetano; Ana Elizabete Silva (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
Trypanosoma cruzi, the etiological agent of Chagas disease, presents a high degree of intraspecific genetic variability, with possible implications for the clinical forms of the disease, like the development of cardiopathy, megaesophagus, and megacolon, alone or in combination. This tissue tropism involved in the pathogenesis of Chagas disease has still not been totally elucidated. Thus, the current review approaches key aspects of T. cruzi genetic diversity, the clinical forms of Chagas disease, and the infection of the host cell by the parasite and the immune response. Other aspects discussed here include the release of immunosuppressive factors by the parasite, acting in the host's immune response pathways; host cell apoptosis inhibition; the pathogenesis of chagasic megaesophagus, which can be related to host-parasite interaction; and finally the association between megaesophagus and increased risk for the development of squamous-cell esophageal carcinoma. However, despite great advances in the understanding of this disease, it is still not possible to establish the true relationship between the parasite's genetic variability and the clinical form of Chagas disease. O Trypanosoma cruzi, agente etiológico da doença de Chagas, apresenta elevado grau de variabilidade genética intra-específica, com possíveis implicações na forma clínica da doença, como o desenvolvimento de cardiopatia, do megaesôfago e do megacólon de forma isolada ou em associação. Este tropismo tecidual envolvido na patogênese da doença não está totalmente esclarecido. Assim, nesta revisão são abordados alguns aspectos referentes à diversidade genética dos parasitas isolados, às formas clínicas da doença de Chagas, ao processo de infecção do parasita na célula hospedeira e resposta imune. Outros aspectos também são enfocados, como os fatores imunossupressivos liberados pelo parasita que atuam na regulação das respostas imunes, a inibição da apoptose da célula hospedeira, assim como da patogênese do megaesôfago chagásico que pode estar relacionada à interação hospedeiro- parasita e sua associação com risco aumentado para o desenvolvimento do carcinoma epidermóide do esôfago. Porém, apesar dos avanços no entendimento desta doença, ainda não é possível estabelecer o verdadeiro perfil da variabilidade genética do parasita com a forma clínica da doença de Chagas.